Gut Content Analysis of Oreochromis niloticus and Chanda nama of Begnas Lake, Kaski, Nepal - Husen, Md. Akbal; Basnet, Alisha; Shahi, Rabina; Khanal, Naresh (International Journal of Applied Sciences and Biotechnology, 2024)
Gut content analysis provides insights into fish species' feeding preferences, tropical interaction, and geographical and seasonal variations in their diets. Guts of Oreochromis niloticus and Chanda nama were analyzed and index of preponderance (IP) was calculated. IP depicts that in O. niloticus, phytoplankton (61.92%) was the most commonly consumed food followed by zooplankton (24.39%), debris, sand (12.57%), nematodes (0.7%) and hatchling (0.42%), In C. nama, micro-crustaceans (48.82%) contributed the most for total volume of food items, followed by scales (37.76%), insects (13.53%), and phytoplankton (0.29%). Begnas lake supports 28 phytoplankton and 12 zooplankton species out of which 24 phytoplankton, seven zooplankton species and seven phytoplankton and four zooplankton species were found in O. niloticus gut and C. nama gut respectively. O. niloticus's diverse feeding habits and C. nama's lepidophagous behavior have caused challenges for native fish, which may be reason for decline in native fish population. Int. J. Appl. Sci. Biotechnol. Vol 12(4): 215-223.